Hungary : Staff Report for the 2006 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2006)
The principal policy task in Hungary is to place public finances on a sound footing. For monetary policy, the challenge is to identify one-off inflationary influences, communicate these to the public and financial markets, and deal with second-round effects. From a risk-management perspective, a floating exchange rate regime is best suited to Hungary's present needs. Although the banking sector has valuable safeguards, recent trends call for more proactive supervision and regulation. Improving labor market performance and enhancing competitiveness are tied in important ways to fiscal reforms.